2011
DOI: 10.4317/medoral.17368
|View full text |Cite
|
Sign up to set email alerts
|

Variations in teaching of removable partial dentures in Spanish dental schools

Abstract: Objectives: Despite the increasing demand for implant-based treatments, removable partial dentures (RPDs) are frequently used in the oral rehabilitation of partially dentate patients. Furthermore, the Bologna Declaration Agreement (1999) promotes the freedom of movement both of students among dental schools and of graduates across the European Union (EU). Given that inconsistency in teaching among dental schools may lead to confusion, this study aimed to evaluate the status of teaching and clinical experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Prosthodontic training is one of the largest components of dental curricula, so gaining competence in prosthodontics is essential. The current profile of the European dentist states that “a dentist must be competent at designing effective indirect restorations, anterior and posterior crowns, bridges, complete and partial dentures, including a combination of fixed and removable dentures, and occlusal splints, and undertaking some of these procedures as is relevant to the country of practice.” 7 Most surveys of education in prosthodontics have been oriented towards clinical materials and techniques, 8 10 preclinical skills, 11 and teaching strategies for complete 12 or partial dentures, 13 but only one study has addressed students’ perceptions of their own clinical competence for treating prosthodontic patients 14 . The aim of our study was to compare the perceived competence for treating prosthodontic patients of two samples of fourth‐year dental students: those educated using traditional methodologies and those educated using PBL.…”
mentioning
confidence: 99%
“…Prosthodontic training is one of the largest components of dental curricula, so gaining competence in prosthodontics is essential. The current profile of the European dentist states that “a dentist must be competent at designing effective indirect restorations, anterior and posterior crowns, bridges, complete and partial dentures, including a combination of fixed and removable dentures, and occlusal splints, and undertaking some of these procedures as is relevant to the country of practice.” 7 Most surveys of education in prosthodontics have been oriented towards clinical materials and techniques, 8 10 preclinical skills, 11 and teaching strategies for complete 12 or partial dentures, 13 but only one study has addressed students’ perceptions of their own clinical competence for treating prosthodontic patients 14 . The aim of our study was to compare the perceived competence for treating prosthodontic patients of two samples of fourth‐year dental students: those educated using traditional methodologies and those educated using PBL.…”
mentioning
confidence: 99%
“…Over the past few years, emphasis has been placed worldwide to document the trends in teaching practices in undergraduate dental schools 8,12,18,19 . A few of the developed countries have even carried out follow‐up studies after a couple of years to assess changes, if any, in the teaching practices 15,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Castillo de Oyagüe et al (9) reported that the duration of the preclinical course for removable partial dentures is clearly shorter in Spain, in comparison with U.S. and Great Britain. However, the mean number of lecture hours reported for U.S dental schools (6) (28 hours, ranging from 12 to 80) is similar to what was observed here.…”
Section: Discussionmentioning
confidence: 99%